Words Spoken by Osiris or the Ibis? An Ibis Coffin with a Hieroglyphic Inscription in the Macquarie University Museum of Ancient Cultures - Coussement, Sandra (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
The article discusses an unprovenanced Ptolemaic lid of an ibis coffin from the collection of the Macquarie University Museum of Ancient Cultures (Sydney). Various aspects suggest that it originates from the ibis cemetery in Tuna El-Gebel. The lid bears a demotic and a hieroglyphic inscription, which are both transliterated, translated and provided with detailed commentary. The demotic inscription includes the usual practical information but the hieroglyphic text is exceptional. It contains the first part of chapter 72 of the Book of the Dead. So far, no other ibis coffin with a similar hieroglyphic text is known. Special attention goes to the peculiar introduction of the chapter on this lid, leaving it unclear who should utter the words following Dd mdw jn, or on whose behalf.